2022
DOI: 10.3390/antiox11020177
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Reduces Ischemia-Reperfusion Injury Induced Endothelial Cell Damage of Arterial Grafts in a Rodent Model

Abstract: Long-term graft patency determines the prognosis of revascularization after coronary artery bypass grafting (CABG). Ischemia-reperfusion (I/R) injury of the graft suffered during harvesting and after implantation might influence graft patency. Aspirin, a nonsteroidal anti-inflammatory drug improves the long-term patency of vein grafts. Whether aspirin has the same effect on arterial grafts is questionable. We aimed to characterize the beneficial effects of aspirin on arterial bypass grafts in a rodent revascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our group has identified some promising drugs for this aim in experimental models ( 8 , 9 ). We have shown in a rat model that treatment with aspirin prior to arterial revascularization significantly reduced the functional and morphological damage suffered by free arterial grafts ( 10 ). As many patients take aspirin prior to CABG and there is a debate whether or not this medication should be discontinued before the operation, the findings of our experiment could be clinically highly relevant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has identified some promising drugs for this aim in experimental models ( 8 , 9 ). We have shown in a rat model that treatment with aspirin prior to arterial revascularization significantly reduced the functional and morphological damage suffered by free arterial grafts ( 10 ). As many patients take aspirin prior to CABG and there is a debate whether or not this medication should be discontinued before the operation, the findings of our experiment could be clinically highly relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly divided into the following groups: (1) non-transplanted control group (ntCo, n = 8): rats received 1% methylcellulose vehicle, aortic transplantation was not carried out; (2) transplanted control group (tCo, n = 8): donor rats received 1% methylcellulose vehicle followed by aortic arch transplantation into the recipient rats ( n = 8); (3) aspirin group (Asp): donor rats ( n = 8) were treated with Asp (115 mg/kg), then aortic arches were transplanted into the recipient rats ( n = 8); (4) zinc-aspirin (ZnAsp) group: donor rats ( n = 8) were treated with zinc-aspirin (100 mg/kg), with subsequent aortic arch transplantation into the recipient rats ( n = 8) ( Figure 1 ). As we have hypothesized an add on effect of zinc to the already demonstrated beneficial effect of aspirin in graft protection ( 10 ), and previous results have shown that zinc-aspirin complex exerts a more beneficial effect than zinc alone against the endothelial damage-driven neointima formation ( 13 ), we have decided not to include a group with zinc treatment alone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant property was also related to the ability of aspirin to enhance the transcription of genes encoding for these antioxidant enzymes (CAT, SOD) [ 126 ]. In two models of ischemia-reperfusion injury administration, aspirin led to a significant reduction in nitro-oxidative stress and an improvement of endothelial function [ 128 , 129 ]. Moreover, in one study, aspirin antioxidant properties protected from oxidative stress-induced DNA strand breaks [ 130 ].…”
Section: Antioxidant Effects Of Antiplatelet Drugsmentioning
confidence: 99%